The Principles and Practice of International Commercial Arbitration. - Moses, Margaret L. (Cambridge : Cambridge University Press, 2012)
Explains how and why arbitration works, offering comprehensive coverage of basic requirements.
9. Waiver of State Immunity10. Multiparty Agreements; C. CONCLUSION; CHAPTER FOUR: Applicable Laws and Rules; A. IMPORTANCE OF THE LAW; B. DELOCALIZATION V. TERRITORIALITY; 1. Arguments Favoring Delocalization; 2. Arguments Opposing Delocalization; 3. Some Modern Approaches to Delocalization; a. Sports Arbitrations; b. Online Arbitrations; C. THE LEX MERCATORIA; 1. Definition of the Lex Mercatoria; 2. Application of the Lex Mercatoria; a. Contracts between States; b. Contracts between a State and a Private Company; D. THE PARTIES' CHOICE OF LAW; 1. The Law Governing the Arbitral Proceedings.
2. The Rules Governing the Arbitral Proceedings.
Includes bibliographical references and index.
Print version record.
Keywords: International commercial arbitration; LAW -- International; International commercial arbitration